Travessia. The audiovisual fabulation of a malunga being (Portuguese version) - Castro Simões, Letícia (Nawi, 2023)
This article debates the short film Travessia, by Bahian filmmaker Safira Moreira, and aims to analyze the audiovisual operation around the construction of a rhizomatic subject, a concept proposed by philoso- phers Gilles Deleuze and Félix Guattari, in resonance with a malungo subject, a historical concept brought here by historian João José Reis. The construction of this multiple being in subjectivity and historicity, according to this analysis, could be observed from the exercise of self-fabulation exercised by the narrator of the short film. Thus, this text seeks to answer the following question: could the audiovisual writing carry out the writing of a multiple subject, divided into many, formed by thousands?